Peak Expiration Flow Prediction Value In The Elderly With The Tai Chi Training - Hanitami, Theresia A; Mellow, Prettysun A; Wattimena, Inge (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: With increasing age, the elderly is more vulnerable to various physical disorders. One of them is a decrease in respiratory system function due to decreased respiratory muscle mass. Tai Chi training can be used as a health facility to maintain an excellent respiratory system. Purpose: Find out the difference between peak expiration flow prediction values in the elderly who do and do not participate in Tai Chi training. Method: This research used an observational analytic method with a cross-sectional design and used purposive sampling technique. The sample of this research was the elderly aged 6075 years who meet the inclusion criteria APE measurements were carried out three times, and the highest value was taken. Data were analyzed using the Mann-Whitney test with a computer program. Results: The data showed that APE value in the elderly who participated in Tai Chi training was 319.3 ± 91.42 while the elderly who did not take Tai Chi training was 265.6 ± 67.04. Statistical test results showed significant difference Conclusion: Based on Mann Whitney's statistical calculations, it can be seen that the significance value or p-value is 0.036 <0.05. It means that there is a significant difference in the average predicted value of peak expiratory flow between elderly who take Tai Chi training with elderly who do not take Tai Chi training, where APE in the elderly who practice Tai Chi is greater than the elderly who do not practice Tai Chi.